A study of virtual private networks security issues and restrictions - Saritha, A.; RamaSubba Reddy, B.; Suresh Babu, A. (International Journal of Engineering and Technology, 2018)
VPN also called as Virtual Private Network serves as a communication network that supports secure data transmission in a public or an unsecured network using several technologies. A connection that is virtual is established among the users who are globally dispersed and are connected through the public or shared network (eg: Internet). Though virtual network is within the public network, it still gives the end-user a feeling of a private connection. This paper explains the concepts of core VPN technology. Security threats posed for VPN environment are discussed in detail and that care must be taken to handle these threats while implementing a virtual private network.